2008
DOI: 10.1103/physrevlett.100.213201
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Effects in the Neutralization ofHe+Ions in the Low Energy Ion Scattering Regime

Abstract: Investigating possible crystal effects in ion scattering from elemental surfaces, measurements of the positive ion fraction P+ are reported for He+ ions scattered from single and polycrystalline Cu surfaces. In the Auger neutralization regime, the ion yield is determined by scattering from the outermost atomic layer. For Cu(110) P+ exceeds that for polycrystalline Cu by up to a factor of 2.5, thus exhibiting a strong crystal effect. It is much less pronounced at higher energies, i.e., in the reionization regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…It is presented together with the linear fit of a dataset acquired for a polar scan at E < E th exhibiting clear 1/v ⊥ -scaling (see Fig.3). Similar to the data presented for Cu(100) in [12] (2) is not sufficient to describe the observations. Similar to the high energy data presented for Cu(100) in [12] for the data shown in Fig.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…It is presented together with the linear fit of a dataset acquired for a polar scan at E < E th exhibiting clear 1/v ⊥ -scaling (see Fig.3). Similar to the data presented for Cu(100) in [12] (2) is not sufficient to describe the observations. Similar to the high energy data presented for Cu(100) in [12] for the data shown in Fig.…”
Section: Resultssupporting
confidence: 68%
“…Similar to the data presented for Cu(100) in [12] (2) is not sufficient to describe the observations. Similar to the high energy data presented for Cu(100) in [12] for the data shown in Fig. 4a the resulting P + values are virtually identical for double alignment conditions, i.e.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The studies in [156] revealed non-negligible differences in the ion fractions of He + after scattering from Cu (110), (100) and polycrystalline surfaces, demonstrating that the so-called "matrix effects" have indeed to be considered in the analysis of low-energy ion scattering data for studies on the composition of solid surfaces. In this section we will compare experimental measurements of ion fractions and energy gains with theoretical calculations for these magnitudes using the Auger neutralization rates presented in section 3.…”
Section: Comparison Of Theory and Experimentsmentioning
confidence: 99%